2006
DOI: 10.1086/507329
|View full text |Cite
|
Sign up to set email alerts
|

ASpitzer Space TelescopeInfrared Spectrograph Spectral Atlas of Luminous 8 μm Sources in the Large Magellanic Cloud

Abstract: We present an atlas of Spitzer Space Telescope Infrared Spectrograph ( IRS) spectra of highly luminous, compact, mid-IR sources in the Large Magellanic Cloud. Sources were selected on the basis of IR colors and 8 m (Midcourse Space Experiment) fluxes indicative of highly evolved, intermediate-to-high-mass stars with current or recent mass loss at large rates. We determine the chemistry of the circumstellar envelope from the mid-IR continuum and spectral features and classify the spectral types of the stars. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 52 publications
11
76
0
Order By: Relevance
“…However, the investigations of Oksala et al (2013) revealed that the chemical composition of the ejecta, in particular the enrichment in 13 C, better agrees with a pre-RSG scenario. This is also the case for LHA 120-S 73, although it shows the strongest enrichment in 13 C. Additional support for a less evolved state is provided by the spectral energy distribution of the dust, which is clearly distinct from those of (post-)RSGs (see, e.g., Buchanan et al 2006). Furthermore, LHA 120-S 73 is a point source in Spitzer IRAC/MIPS images without any diffuse nebulosity (Kastner et al 2010).…”
Section: Evolutionary State Of Lha 120-s 73mentioning
confidence: 54%
“…However, the investigations of Oksala et al (2013) revealed that the chemical composition of the ejecta, in particular the enrichment in 13 C, better agrees with a pre-RSG scenario. This is also the case for LHA 120-S 73, although it shows the strongest enrichment in 13 C. Additional support for a less evolved state is provided by the spectral energy distribution of the dust, which is clearly distinct from those of (post-)RSGs (see, e.g., Buchanan et al 2006). Furthermore, LHA 120-S 73 is a point source in Spitzer IRAC/MIPS images without any diffuse nebulosity (Kastner et al 2010).…”
Section: Evolutionary State Of Lha 120-s 73mentioning
confidence: 54%
“…Only the EROs from Program 40650 (Gruendl et al 2008) are affected. Sloan et al (2008) Evolved stars in the LMC and SMC 1094 F. Kemper AGB evolution in the LMC (and Galaxy) 3277 M. P. Egan Sloan et al (2006), Kraemer et al (2016) Infrared-bright sample in the SMC 3426 J. H. Kastner Buchanan et al (2006) Infrared-bright sample in the LMC 3505 P. R. Wood Zijlstra et al (2006), Lagadec et al (2007) AGB stars in the LMC and SMC 3591 F. Kemper Leisenring et al (2008) Evolved O-rich stars in the LMC 30155 J. R. Houck…”
Section: Spectramentioning
confidence: 99%
“…They were all obtained in 2008; individual epochs are listed in Table 2. Alcock et al 2001 and 5 in the SMC 2 , Tisserand et al 2004) as well as 5 RCB candidates selected either from their optical spectra (Morgan et al 2003) 3 or their mid-infrared featureless spectra (Kraemer et al 2005;Buchanan et al 2006). The EROS-2 light curves of all these objects, if catalogued, are available at the following URL: http://eros.in2p3.fr/ Variables/RCB/RCB-LMC.html…”
Section: Observational Datamentioning
confidence: 99%